Net nestrality regulation in the US and Chile: Relevant aspects concerning regulation in technological markets from analyzing two concrete regulatory experiences - Zink P., Manfred (Derecho Público Iberoamericano, 2013)
The author proposes to undertake an analysis of the regulatory processes of the introduction of the net neutrality principle in Chile and the United States in order to establish some basic principles about the role of the legislature and the administrative agency in the regulation of technologies, starting from real experience. The analysis leads to the conclusion that the legislature, being the main institution designed to encompass and concretize the political debate (and, therefore, different normative or moral positions) onto mandatory rules, must have its place in the regulation of technologies. But in the same way, the examination indicates that the extent of congressional action should be determined precisely by its main role of being the forum comprising political divergence or debate, avoiding, if possible, to dwell into complex technical issues.